The Influence of Environmental Awareness on Purchase Intention in Buying Green FMCG Product (Journal of Business and Management, 2021)
Environmental conditions getting worse, but, FMCG industry in Indonesia, is contributing to environmental damage because the majority of plastic waste is produced by FMCG producers. Whereas most people are aware of environmental issues and value more for brands that care about the environment. In order to satisfy the consumers which impacts the brand or company sustainability, it is necessary to understand the consumer’s behavior through the consumer’s purchase intention. Therefore, this research aims to identify green FMCG consumer behavior and to identify the role of environmental awareness on consumer purchase intentions towards green FMCG products. This research uses a quantitative approach through an online questionnaire survey, analyzed using descriptive analysis and PLS-SEM. This research focuses on FMCG consumers who have environmental awareness, are interested in green products, and are domiciled in JABODETABEK or Bandung Raya. The result indicates that consumers get information from stores and social media, buy the products in the store, and snacks as their most frequently purchased product. The role of environmental awareness is to influences purchase intention indirectly through Attitudes, Subjective Norms, and Perceived Behavioral Control.Keywords: Environmental Awareness, Purchase Intention, Green Products, FMCG